A8.06 Microrna-125b expression in PBMCS is inversely associated with disease activity in patients with early rheumatoid arthritis. (24th February 2016) - Hruskova, V; Jandova, R; Vernerova, L; Mann, H; Prajzlerova, K; Filkova, M; Pavelka, K; Vencovsky, J; Senolt, L
Abstract : Background and objectives: MicroRNAs (miRNAs) are small RNAs that regulate gene expression by targeting mRNA. It was proved that some miRNAs are significantly deregulated in rheumatoid arthritis (RA). MicroRNA-125b negatively regulates expression of TNF-α, which plays a crucial role in RA pathogenesis. The aim of this study was to evaluate the expression of miRNA-125b in peripheral blood mononuclear cells (PBMCs) and its association with disease activity and treatment response in early RA patients. Materials and methods: A total of 58 (42 females; mean age 54.3 ± 16.4 years) early RA patients and 54 (41 females; mean age 50.9 ± 15.11 years) healthy controls (HC) were studied. Total RNA was isolated from PBMCs collected from patients before and after three months of glucocorticoid/disease modifying antirheumatic drugs treatment and from HC. The expression of miRNA-125b was determined by quantitative PCR. RNU44 was used for normalisation. Disease activity was defined using 28-Joint Count Disease activity Score (DAS28-ESR). The expression of miRNA-125b was studied in order to predict treatment response characterised by achieving remission or alternatively low disease activity (DAS28 < 3.2). Results: The expression of miRNA-125b was significantly lower in early RA patients compared to HC (p = 0.001) and increased after three months of therapy (p = 0.006), mainly in responders (p = 0.019). At baseline, miRNA-125b expression negatively correlated with DAS28 (r = -0.462; p = 0.0003). In addition, baseline miRNA-125b expression predicted treatment response after three months which was performed by ROC curve analysis (AUC: 0.663 [95% CI 0.520 to 0.805]; p = 0.048). Conclusion: Monitoring of miRNA-125b could be used as a biomarker of disease activity and treatment response in early RA. Acknowledgement: IGA project No NT 14498; GAUK-367615.